The Use of Financial Technology by ZISWAF Institutions in the Digital Era - Ayu Sinta Indriani; Farhan Dharmawan; Riki Kurniawan; Rizky Fadhilah Ahmad (Nuban Jagadhita Centre, 2025)
Introduction: The development of digital technology, particularly financial technology (fintech), has driven significant transformation in the management of Islamic social finance, including in Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) institutions. Objective: This study aims to analyze the role of fintech in enhancing the effectiveness of ZISWAF fund collection, transparency, and distribution, and to identify challenges and strategies to optimize its implementation in the digital era. Method: A qualitative approach was used, involving library research and secondary data from official institutional reports, regulations, and relevant scientific literature. The analysis was conducted using a descriptive-thematic approach based on the Technology Acceptance Model (TAM), the Diffusion of Innovations (DoI) theory, trust theory, and institutional theory. Results: The study findings indicate that the use of fintech significantly improves operational efficiency, expands public access to Islamic philanthropic services, and strengthens the transparency and accountability of ZISWAF institutions. Collaboration with digital platforms has proven effective in boosting public trust and accelerating technology adoption. However, there are several major challenges, such as low digital literacy, limited human resources, infrastructure gaps between urban and rural areas, and insufficient regulatory support. Implication: This study underscores the importance of a systemic and collaborative approach in the development of ZISWAF fintech, through human resource capacity building, the enhancement of digital literacy, the formulation of adaptive policies, and synergy among the government, ZISWAF institutions, and the fintech sector. Thus, fintech integration is not merely a technical tool but also a transformational strategy for realizing modern, inclusive, and sustainable Islamic social finance governance.